Chromosomes and cancer cells - Thompson, Sarah L. (2011)
Two prominent features of cancer cells are abnormal numbers of chromosomes (aneuploidy) and large-scale structural rearrangements of chromosomes. These chromosome aberrations are caused by genomic instabilities inherent to most cancers. Aneuploidy arises through chromosomal instability (CIN) by the persistent loss and gain of whole chromosomes. Chromosomal rearrangements occur through chromosome structure instability (CSI) as a consequence of improper repair of DNA damage. The mechanisms that cause CIN and CSI differ, but the phenotypic consequences of aneuploidy and chromosomal rearrangements may overlap considerably. Both CIN and CSI are associated with advanced stage tumors with increased invasiveness and resistance to chemotherapy, indicating that targeted inhibition of these instabilities might slow tumor growth. Here, we review recent efforts that define the mechanisms and consequences of CIN and CSI.